(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the prevalence of dyslipidemia and associated factors among hypertensive patients in Dong Thap Province. Subjects and Methods: A cross-sectional descriptive study with analytical components was conducted on 1,200 hypertensive patients in Dong Thap Province from June 2022 to December 2024. Results: The prevalence of dyslipidemia among hypertensive patients was 89.50%. The proportions of elevated total cholesterol, elevated triglycerides, elevated LDL-C, and reduced HDL-C were 75.25%, 87.0%, 30.83%, and 17.67%, respectively. Dyslipidemia was more common in males (OR = 1.71; p = 0.003). Patients with an educational level of primary school or below had a 3.71-fold higher risk of dyslipidemia compared with those with secondary school education or higher (p < 0.001). Physically inactive patients had a 2.45-fold higher risk of dyslipidemia compared with physically active individuals (p < 0.001). Individuals who frequently consumed salt-rich foods (≥ 5 days/week) had a 2.31-fold higher risk of dyslipidemia compared with those who consumed such foods less frequently (< 5 days/week) (p < 0.001). Participants with BMI ≥ 23 had a 4.63-fold higher risk of dyslipidemia compared with those with BMI < 23 (p = 0.001). Non-adherent patients had a 3.07-fold higher risk of dyslipidemia compared with treatment-adherent patients. Conclusion: Dyslipidemia is highly prevalent among hypertensive patients in Dong Thap Province, particularly hypertriglyceridemia and elevated total cholesterol. Dyslipidemia was more common among males, physically inactive individuals, those who frequently consumed salt-rich foods, overweight and obese individuals (BMI ≥ 23), and patients with poor treatment adherence.